Effects of empagliflozin on right ventricular adaptation to pressure overload - Axelsen, Julie S.; Nielsen-Kudsk, Anders H.; Schwab, Janne; Ringgaard, Steffen; Nielsen-Kudsk, Jens Erik; de Man, Frances S.; Andersen, Asger; Andersen, Stine (Frontiers in Cardiovascular Medicine, 2023)
Background: Right ventricular (RV) failure is the prime cause of death in patients with pulmonary arterial hypertension. Novel treatment strategies that protect the RV are needed. Empagliflozin, a sodium-glucose co-transporter-2 inhibitor, shows cardioprotective effects on the left ventricle in clinical and preclinical studies, but its direct effects on RV remain elusive. We investigated the effects of empagliflozin on RV dysfunction induced by pulmonary trunk banding (PTB).Methods: Male Wistar rats (116±10 g) were randomized to PTB or sham surgery. One week after surgery, PTB animals received empagliflozin mixed into the chow (300 mg empagliflozin/kg chow; PTB-empa, n=10) or standard chow (PTB-control, n=10). Sham rats (Sham, n=6) received standard chow. After five weeks, RV function was evaluated by echocardiography, cardiac MRI, and invasive pressure-volume measurements.Results: PTB caused RV failure evident by decreased cardiac output compared with sham. PTB-empa rats had a 49% increase in water intake compared with PTB-control yet no differences in hematocrit or blood glucose. Treatment with empagliflozin decreased RV end-systolic pressures without any changes in RV cardiac output or ventricular-arterial coupling (Ees/Ea). The decrease in RV endsystolic pressure was complemented by a slight reduction in RV cross sectional area as a sign of reduced hypertrophy. Load-independent measures of RV systolic and diastolic function were not affected in PTB-empa rats compared with PTB-control. This is a provisional file, not the final typeset article Conclusion: Empagliflozin treatment reduced RV end-systolic pressure in RV failure induced by pressure overload. Further studies are needed to elucidate whether this simply relates to a diuretic effect and/or additional independent beneficial RV effects.